2023
DOI: 10.1051/0004-6361/202245364
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicity of northern bright O-type stars with optical long baseline interferometry

Abstract: Context. The study of the multiplicity of massive stars gives hints on their formation processes and their evolutionary paths, which are still not fully understood. Large separation binaries (>50 milliseconds of arc, mas) can be probed by adaptive-optics-assisted direct imaging and sparse aperture masking, while close binaries can be resolved by photometry and spectroscopy. However, optical long baseline interferometry is mandatory to establish the multiplicity of Galactic massive stars at the separation gap b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…In terms of detecting binary companions, CHARA/MIRC (-X) routinely reaches a contrast ratio of 1% or lower (corresponding to a magnitude difference of more than 5 mag; e.g., De Furio et al 2022;Klement et al 2022b;Lanthermann et al 2023), with the best-performance limit being ∼0.3% (Δmag ∼ 6.4; Gallenne et al 2015). Thanks to the six telescopes and the resulting dense coverage of the (u, v) plane, CHARA is capable of detecting faint companions with snapshot observations, i.e., 10-20 minute integrations of fringes on the science target.…”
Section: The Chara Arraymentioning
confidence: 99%
“…In terms of detecting binary companions, CHARA/MIRC (-X) routinely reaches a contrast ratio of 1% or lower (corresponding to a magnitude difference of more than 5 mag; e.g., De Furio et al 2022;Klement et al 2022b;Lanthermann et al 2023), with the best-performance limit being ∼0.3% (Δmag ∼ 6.4; Gallenne et al 2015). Thanks to the six telescopes and the resulting dense coverage of the (u, v) plane, CHARA is capable of detecting faint companions with snapshot observations, i.e., 10-20 minute integrations of fringes on the science target.…”
Section: The Chara Arraymentioning
confidence: 99%
“…The three companions covered here were previously known only from RV and/or astrometric observations, such that our results represent their first direct detections and provide the first spectra for the companions. Though KPIC VFN alone can provide a detection, in this Letter we complement the VFN observations with CHARA observations using the MIRC-X and MYSTIC beam combiners (Anugu et al 2020;Setterholm et al 2023), which have a demonstrated history of success at these angular separations (e.g., Roettenbacher et al 2015aRoettenbacher et al , 2015bThomas et al 2021;De Furio et al 2022;Lanthermann et al 2023). This allows us to validate the VFN performance in this first demonstration against CHARA's well-established performance.…”
Section: Introductionmentioning
confidence: 74%
“…Spectroscopic and imaging optical observations have shown that 70% to 90% massive stars have at least one companion (Sana et al 2014;Lanthermann et al 2023). A survey of radial velocities of 16 embedded high-mass stars revealed that at least 20% of the targets are close binaries (Apai et al 2007).…”
Section: Discussionmentioning
confidence: 99%